The Role Of Teachers In Developing Discipline Attitudes In Elementary School Students - Amanda Syahba Billa; Yustia Suntari; Chrisnaji Banindra Yudha (PGMI IAIN Lhokseumawe, 2025)
Teachers have a strategic role in the world of education, not only delivering learning materials, teachers also play a role in providing good examples for students. In practice, teachers are expected to be good examples for students, especially in instilling the values ​​of discipline. However, over time the discipline of elementary school students has decreased. This can be seen from the number of students who do not obey the rules at school. The purpose of this study is to explain the role of teachers in fostering a disciplined attitude in students at the elementary school level. The method used in this study is descriptive qualitative with data collection in the form of observation, interviews, and studies of relevant research literature. The results of this study indicate that teachers have a very important role in fostering a disciplined attitude in students. Through various methods such as giving examples, providing motivation, and implementing rewards and punishments. Thus, the role of teachers is very important in fostering a disciplined attitude in elementary school students